Technology-facilitated Sexual Violence in South Korea: A Content Analysis of a Website for Victims - Kim, SooJeong (Violence against women, 2024)
Technology-facilitated sexual violence (TFSV) is an emerging form of gender-based violence. An understanding regarding the circumstance of TFSV and related health outcomes is limited. This qualitative study analyzed postings from an anonymous Korean website on which women suffering from TFSV freely posted messages asking for help and voicing concerns. Victims made efforts to solve problems that remained unresolved, thereby creating difficulties in their daily lives, and compelling them to quit jobs or break social relationships. They reported mental health concerns including suicide ideation, anxiety, frustration, sleep disorders, and depression. Results infer the imperative nature of research, intervention, and political action.